KOMBINASI TANGKI AERASI DAN UPFLOW BIOFILTER DALAM MENDEGRADASI BAHAN ORGANIK (BOD, TSS, TDS) LIMBAH CAIR INDUSTRI TEMPE - Tuhu Agung Rahmanto; M Arif Wibowo (EnviroUS, 2021)
Almost in every city in Indonesia there are many home-scale tempe industries. These industries have not yet treated their waste, which has resulted in river water pollution. Limited funding becomes an obstacle when industrial owners build wastewater treatment facilities. The construction of an appropriate and cheap wastewater treatment facility will be of great benefit to them. The combination of an aerobic reactor and biofilter media is a biological waste water treatment process using filter media. This study used an aerobic system with the variations used were detention time for 24, 48, 72, 96, 120 hours and a combination of a consortium of microorganisms. The parameters analyzed were BOD, TSS, and TDS. From the research, it was found that the optimal removal efficiency with a consortium of microorganisms in reactor A with a residence time of 120 hours and the final results were BOD 95.58%, TSS 24.82%, and TDS 48.95%.